Insulin Resistance and Chronic Cardiovascular Inflammatory Syndrome - Fernández-Real, José Manuel; Ricart, Wifredo (Endocrine reviews, 2003)
Insulin resistance is increasingly recognized as a chronic, low-level, inflammatory state. Hyperinsulinemia and insulin action were initially proposed as the common preceding factors of hypertension, low high-density lipoprotein cholesterol, hypertriglyceridemia, abdominal obesity, and altered glucose tolerance, linking all these abnormalities to the development of coronary heart disease. The similarities of insulin resistance with another inflammatory state, atherosclerosis, have been described only in the last few decades. Atherosclerosis and insulin resistance share similar pathophysiological mechanisms, mainly due to the actions of the two major proinflammatory cytokines, TNF-α and IL-6. Genetic predisposition to increased transcription rates of these cytokines is associated with metabolic derangement and simultaneously with coronary heart disease. Dysregulation of the inflammatory axis predicts the development of insulin resistance and type 2 diabetes mellitus. The knowledge of how interactions between metabolic and inflammatory pathways occur will be useful in future therapeutic strategies. The effective administration of antiinflammatory agents in the treatment of insulin resistance and atherosclerosis is only the beginning of a promising approach in the management of these syndromes.